Legal norms in corrections - Cohen, Fred.; United States. President's Commission on Law Enforcement and Administration of Justice ([Washington] : President's Commission on Law Enforcement and Administration of Justice, 1967)
For the purpose of this paper, some observations about the characteristics of the general trend of reexamination and change of the criminal process will serve as a foundation for the more detailed discussion of the correctional process. In this work, inquiry into the social fabric was deemed less important than the effort to tease out the values implicit in decisions made under our Constitution.
Chapter 1. Introduction and general principles -- Chapter 2. Probation and parole. A. Granting -- B. Supervision -- C. Revocation -- Chapter 3. Imprisonment. A. Access to the courts -- B. Prison life and legal limitation -- C. Legal process and prison life -- Footnotes.
"Submitted to the President's Commission on Law Enforcement and Administration of Justice."
Cover title.
Includes bibliographical references.
Mode of access: Internet.
Keywords: Probation -- United States; Parole -- United States; Prisoners -- Legal status, laws, etc. -- United States